Reactive Oxygen Species in Anticancer Immunity: A Double-Edged Sword - Wang, Jie; Liu, Ning; Jiang, Hongfei; Li, Qian; Xing, Dongming (Frontiers in Bioengineering and Biotechnology, 2021)
Reactive oxygen species (ROS) are critical mediators in many physiological processes including innate and adaptive immunity, making the modulation of ROS level a powerful strategy to augment anticancer immunity. However, current evidences suggest the necessity of a deeper understanding of their multiple roles, which may vary with their concentration, location and the immune microenvironment they are in. Here, we have reviewed the reported effects of ROS on macrophage polarization, immune checkpoint blocking (ICB) therapy, T cell activation and expansion, as well as the induction of immunogenic cell death. A majority of reports are indicating detrimental effects of ROS, but it is unadvisable to simply scavenge them because of their pleiotropic effects in most occasions (except in T cell activation and expansion where ROS are generally undesirable). Therefore, clinical success will need a clearer illustration of their multi-faced functions, as well as more advanced technologies to tune ROS level with high spatiotemporal control and species-specificity. With such progresses, the efficacy of current immunotherapies will be greatly improved by combining with ROS-targeted therapies.